Determination of Vitamin C Levels in Various Chilli (Capsicum sp) Varieties and In-Silico Activity Assessment - Dwisari, Fath; Dermawan, Abdurraafi' Maududi (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Chili peppers are acknowledged as one of the fruits endowed with a notable vitamin C content, a crucial nutrient integral to various physiological processes. These include collagen synthesis, bone and tooth formation, wound healing, and bolstering the immune system's defense against infections. Vitamin C, as a water-soluble compound, is susceptible to degradation when exposed to atmospheric conditions. Hence, careful preservation of chili peppers is imperative to maintain their vitamin C levels. The primary objective of this study is to discern the concentrations of vitamin C within three distinct stages of chili pepper ripeness: young, semi-ripe, and fully ripe. The methodology employed in this investigation entails UV-Vis Spectrophotometry, with a maximal wavelength for vitamin C quantification established at 265 nm. This approach yielded absorbance values of 0.696, 0.564, and 0.478 for the respective stages. Quantitative analysis reveals that the vitamin C concentrations in young, semi-ripe, and fully ripe chili peppers are 8.1397 ppm, 5.9559 ppm, and 4.5313 ppm, respectively. These findings unequivocally demonstrate that vitamin C content is significantly higher in young chili peppers when compared to their semi-ripe and fully ripe counterparts. The docking results for capsaicin ligands yielded Gibbs energy (?G), Ki and IC50 value -6.14 kkal/mol, 31.34 µm and 19.143 ppm, respectively. The result indicate that capsaicin exhibited good interaction to catalytic site of glycogen phosphorylase which could serve as a potential antidiabetic agent.